PENGARUH METODE PENGERINGAN TERHADAPKARAKTERISTIK FISIKOKIMIA IKAN PARI (Dasyatis sp.) KERING - Faisal Susandi; R. Marwita Sari Putri; Jumsurizal (Marinade, 2020)
Drying is a preservation method by removing or removing air from a material using heat energy. The purpose of this study was to study the interactions and changes in physicochemical characteristics with different drying methods. This study uses a Completely Randomized Design (CRD) with three drying treatmet namely microwave, oven and sunlight. The parameters collected were wet content, ash content, protein content, fat content, salt content, amino acids, TPC (Total Plate Count) and hedonic tests (taste, flavour, color and texture). The results showed a method that was significantly different from wet content, but did not significantly affect ash content, protein content and fat content. While the real storage time for wet content, ash content, protein content, fat content, TPC value and hedonic value. The best combination is oven drying at a temperature of 100â—‹ -130â—‹C for 5 hours with air content of 14.81%, ash content of 2.31%, protein content of 41.87%, fat content of 3.07%, salt content of 4.01%, taste value 9.4, flavour 9.26, color 8.86, texture 8.73 and value of TPC (Total Plate Count) 2.5 x 102